The society of equals: Restoring democratic equality in relations. Issue 4 (March 2014) - Rosanvallon, Pierre
<x xml:space="preserve">Abstract</x> Leading political philosopher Pierre Rosanvallon outlines a reformation of the idea of equality that takes its inspiration from the revolutionary visions of France and the United States while embracing what is good about our modern individualism and diversity.